The Role of Initiatives in Metropolitan Design Strategies Through NYC Case - Çubuk, Gencay (Street Art & Urban Creativity, 2023)
The study first considers urban design, the strategies needed to increase the operability and sustainability of urban design, and the role of initiatives in these, through a literature review. Then, the NYC Design Guidelines for the years 2017-2021 are reviewed and the data here are evaluated together with the previous inferences. The design studies for the metropolitan area provide local solutions that can be successful if they are designed with an understanding that brings together the works of local governments and these initiatives. Routers in urban use are directly related to the fact that a large number of user teams with different purposes can reach areas with high efficiency and experience themselves by adhering to the routers provided by the initiatives. The prominent keywords in the inferences obtained in this section are handled both individually and taking into account the thematic groups they form. The frequencies of the leading themes and the way they are associated make visible the work areas in which the initiatives have a stake. Since the themes in this reading include organic relations both numerically and verbally, it is very important to understand the role of initiatives in the applicability of NYC design criteria, that these representations are fed from contrasts such as proximity-distance, frequency-rareness, as in real life. By filtering the data obtained at each step through the literature review, the next step is taken and a comprehensive framework is presented on the current positioning of the initiatives and how they can be carried into the near future.